2015
DOI: 10.1515/snde-2014-0060
|View full text |Cite
|
Sign up to set email alerts
|

On the relationship between oil and gold before and after financial crisis: linear, nonlinear and time-varying causality testing

Abstract: We examine the causal relationship between crude oil and gold spot prices before and after the recent financial crisis. In the pre-crisis period, causality is linear and unidirectional, running from oil to gold. In the post-crisis period, a bidirectional nonlinear causality relationship emerges. Volatility spillover transpires as the source of nonlinearity during this period. The time path of the causal linkages both for the returns and the levels (cointegration) was assessed via dynamic bootstrap causality an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
50
1
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 26 publications
7
50
1
1
Order By: Relevance
“…Melvin and Sultan (1990) contend that both changes in oil price and political unrests are significant determinants of gold prices volatility. Narayan et al (2010) More recently, Bampinas and Panagiotidis (2015) examined the causal relationship between crude oil and gold spot prices before and after the recent financial crisis via dynamic bootstrap causality analysis. They found that, in the pre-crisis period, causality is linear and unidirectional and running from oil to gold.…”
Section: Oil Price Versus Stock Pricesmentioning
confidence: 99%
See 1 more Smart Citation
“…Melvin and Sultan (1990) contend that both changes in oil price and political unrests are significant determinants of gold prices volatility. Narayan et al (2010) More recently, Bampinas and Panagiotidis (2015) examined the causal relationship between crude oil and gold spot prices before and after the recent financial crisis via dynamic bootstrap causality analysis. They found that, in the pre-crisis period, causality is linear and unidirectional and running from oil to gold.…”
Section: Oil Price Versus Stock Pricesmentioning
confidence: 99%
“…This article differs from similar previous studies in several aspects. First, most of research papers focus on bilateral linkages such as oil versus stock markets (Jones and Kaul, 1996;Sadorsky, 1999;Aloui and jammazi, 2009;Arouri et al, 2012;Mollick and Assefa, 2013;…), oil price versus gold price (Zhang and Wei, 2010;Ewing and Malik, 2013;Bampinas and Panagiotidis, 2015), gold prices versus stock markets (Sumner et al, 2010;Gaur and Bansal, 2010;and Le and Chang, 2012), oil price versus exchange rates (Basher et al, 2012) and other on trilateral linkages such as oil price, exchange rates and stock prices (Sekmen, 2011 ;Olugbenga, 2012;Fratzscher et al, 2014), and gold, foreign exchange and stock market (Shahram et al, 2015). We implement our investigation on the four markets simultaneously.…”
Section: Introductionmentioning
confidence: 99%
“…This is consistent with the findings of Bampinas and Panagiotidis (2016) that energy stocks are a good hedge against inflation. This is also not surprising, as pointed out by Bampinas and Panagiotidis (2015b) who show that, before the recent financial crisis period, oil spot price changes cause gold spot price changes, whereas after the crisis period this effect seems to have weakened.…”
Section: Discussionmentioning
confidence: 62%
“…In this analysis, we are employing DP to allow for nonlinear causality between the UK regional housing markets. For more discussion on the tests and applications, the reader is pointed to Alagidede et al (2011) and Bampinas and Panagiotidis (2014).…”
Section: Methodsmentioning
confidence: 99%